Avaliação quantitativa da água subterrânea no estado de Mato Grosso do Sul - Silva, Caroline Aparecida de Almeida [UNESP] (2012)
The use of groundwater resources in the State of Mato Grosso do Sul is expanding due to population growth, the attractive agricultural, industrial, tourism and advantages in relation to surface water resources. Groundwater can be easily found, as well as surface water, but their quality can be superior, since now many surface waters are very polluted. With increasing demand for groundwater, expand the studies about these natural resources, along with the creation of a decree and a law for the preservation and conservation of these stocks. The State of Mato Grosso do Sul is one of the richest states in Brazil's groundwater resources, being used for urban water supply in 72% of the municipalities. Hence the importance to protect and conserve these groundwater resources. The SANESUL (Basic Sanitation Company of Mato Grosso do Sul) is responsible for the uptake and distribution of groundwater in the state. This work was prepared as a contribution to the State of Mato Grosso do Sul. The database used was sought in the Information System Groundwater - SIAGAS where data were found on the existing wells in the state. The analyzes were made from the information on wells drilled in aquifers in the State of Mato Grosso do Sul, where they were checked local aquifers, flow rates, depths, drilling date, type of use and location of wells. The amount of these existing groundwater wells was also analyzed and found 1346 wells. We estimated the flow of groundwater and the second most important state results are the Serra Geral, Guarani and Bauru, which have respectively 15,554, 10,758 and 8,438 m³ / h flow exploited by summing all the wells drilled in each of these aquifers. With a population assessment of the state along with the number of existing wells, one can see that Mato Grosso do Sul is in development and that some areas need attention so that the emergency water supply remains compatible with the demand. The ...